Paul and the language of faith - Gupta, Nijay K. (William B. Eerdmans Publishing Company, 2020)
"This book will root Paul's love language in its context in the ancient world, where love was seen as affection, loyalty, and generosity; Paul's use is remarkable in making the emphasis one where love is understood as generosity and this, in a culture of reciprocity and mutual expectation"--